2010
DOI: 10.1016/j.neuroscience.2009.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Stress hormone synthesis in mouse hypothalamus and adrenal gland triggered by restraint is dependent on pituitary adenylate cyclase-activating polypeptide signaling

Abstract: Stress responses are elicited by a variety of stimuli and are aimed at counteracting direct or perceived threats to the well-being of an organism. In the mammalian central and peripheral nervous systems, specific cell groups constitute signaling circuits that indicate the presence of a stressor and elaborate an adequate response, ultimately restoring homeostasis. Pituitary adenylate cyclase-activating polypeptide (PACAP) is expressed in central and peripheral parts of these circuits and has recently been ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
106
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(122 citation statements)
references
References 31 publications
10
106
1
3
Order By: Relevance
“…Our finding that PACAP activates the HPA axis confirms previous ones (Agarwal et al, 2005;Norrholm et al, 2005) and is consistent with the very important observation that mice lacking the gene coding for PACAP do not show HPA axis activation following restraint stress (Lehmann et al, 2012;Stroth and Eiden, 2010). Interestingly, we show that the ability of PACAP to activate the HPA axis does not require central CRF receptors, as the CRF receptor antagonist did not block the elevation in circulating corticosterone levels.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our finding that PACAP activates the HPA axis confirms previous ones (Agarwal et al, 2005;Norrholm et al, 2005) and is consistent with the very important observation that mice lacking the gene coding for PACAP do not show HPA axis activation following restraint stress (Lehmann et al, 2012;Stroth and Eiden, 2010). Interestingly, we show that the ability of PACAP to activate the HPA axis does not require central CRF receptors, as the CRF receptor antagonist did not block the elevation in circulating corticosterone levels.…”
Section: Discussionsupporting
confidence: 92%
“…PACAP also induces c-Fos expression and CREB phosphorylation in CRF neurons in the PVN, raising plasma corticosterone levels (Agarwal et al, 2005;Norrholm et al, 2005). These findings, together with the observation that CRF mRNA and corticosterone levels are reduced in PACAPdeficient mice after restraint stress (Stroth and Eiden, 2010), suggest that PACAP might have a physiological role in the regulation of CRF synthesis and activity.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Another possibility is that under long-term PACAP exposure connexin gene expression increases via a PKA-or PKC-dependent mechanism, effectively remodeling the adrenal medulla to support sustained secretion. Indeed, PACAP has been shown to activate a number of stress-related genes on the hour timescale (38,41,49). Although a significant enhancement of connexin gene transcription is unlikely to account for the substantial and rapid enhancement in electrical coupling observed in our study, it seems likely that PACAP stimulates gene expression of connexins under a longer time scale to electrically remodel the adrenal medulla.…”
Section: Discussionmentioning
confidence: 56%
“…In the longer term (Ͼ10 min), PACAP-mediated adrenal excitation further depolarizes the membrane and recruits an L-type Ca 2ϩ influx (35). Ultimately, long-term PACAP excitation elicits a broader modulation of adrenal exocytic function through the activation of secretion-associated genes (38,41,49). More recent studies (9) have suggested a wider role for PACAP in the sympathoadrenal stress response that may include increased intercellular electrical coupling within the medulla.…”
mentioning
confidence: 99%